Caracterizações morfofuncionais testiculares e cardíacas em camundongos knockout para receptor do LDL - FIGUEIREDO, Ariane A.B. (2018)
Variations in lipids and lipoproteins are considered a risk factor for cardiovascular diseases, such as atherosclerosis. This study evaluated the effect of genetic and alimentary dyslipidemia on testicular morphofunctional characteristics and whether its relation with the cardiovascular diseases developed by hyperlipidic diets in genetically modified mice, absent LDL receptor (Ldlr-/-) and wild type mice. In addition to evaluating the replacement of testosterone in the protection of the cardiovascular system of Ldlr-/- mice fed or not with a hyperlipidic diet. In the first study, Ldlr-/- mice were selected, divided into four groups (n = 10): S: animals fed standard diet (Nuvital®) for rodents and without testosterone application; ST: animals fed standard diet (Nuvital®) for rodents and with testosterone application (0.01 ml per week); HL: animals fed a hyperlipid diet (20% total fat, 1.25% cholesterol and 0.5% cholic acid) and without testosterone application; HLT: animals fed a hyperlipid diet (20% total fat, 1.25% cholesterol and 0.5% colic) and with testosterone application (0.01 ml per week). In the analysis of the lipid profile, the mice that received hyperlipidic diets (HL and HLT) presented severe mixed dyslipidemia with increased serum levels of total cholesterol, LDL, VLDL and triglycerides, when compared to the mice of the S and ST groups. However, the HLT group showed an increase in serum HDL levels when compared to the mice in the HL group. The mice from the S and ST groups had increased serum HDL levels in relation to the other groups studied. In the second study, it was observed that the dyslipidemia generated by the LDL receptor deficiency (Ldlr-/-) has a positive relation with the increase in the production of vascular superoxide anions, increased expression of CD40 and FasL in the testis. Genetic deletion of the LDL receptor (Ldlr-/-) in mice associated with a hyperlipidic diet increased both systemic and testicular damage. In conclusion, the metabolic disorders of the lipids generated by the deletion of the LDL gene induced testicular dysfunction, by mechanisms involving oxidative stress, inflammation and apoptosis, impairing spermatogenesis and testicular steroidogenesis. It is also suggested that testosterone may indirectly cause hypertrophy of cardiomyocytes